Pengaruh Teknik Relaksasi Bernafas Terhadap Penurunan Intensitas Nyeri Pada Persalinan Kala I Di Ruang Kebidanan Puskesmas Poasia Kota Kendari - Risqi Wahyu Susanti (STIKes Karya Kesehatan, 2014)
Based on the early survey results, a nurse or other health workers do not the breathing relaxation technique effectively on the patients of confinement. The research question is : ‘Is there any significant effect of breathing relaxation technique on the reducing of intensity of pain in the first phase of confinement in the Obstetrics Room of Clinic at Poasia Kendari?. Breathing relaxation technique is a method which can overcome fear, relieve tension, reduce pain and replace with mental and physical relaxation. This study is a research axperiment with quasi experimental design and nonequivalent control group design. The sample was taken by using Accidental sampling technique with 30 people of sample, in which there are 15 people were given treatment and 15 people of control group were not given the breathing relaxation technique. The data in analyzed by using program SPSS version 15 with a parametric statistical t-test paired and t-test is independent with (α) 0.01. The result obtained from parametric test, t-test paired in the treated group p = 0.000, in the control croup p = 0.0313 while by using t-test, the independent t-test obtained p = 0.000. The result of this study shows that breathing relaxation technique influenced on the reducing of intensity of pain in the confinement on the pain first phase. Keywords: Breathing relaxation technique, pain of intensity, confinement